PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada Karyawan Hotel Patra Jasa Jakarta) - Monica Marsella; Sri Suryoko (Universitas Diponegoro, 2016)
Labor or human resources have an important role in the company in order to achieve success.Therefore, companies must consider the factors that may affect the performance of employees, such ascompensation and working environment. Achievement of employee performance Patra Jasa Jakarta said notoptimal in which the employee's performance increased in 2012 but decreased performance in 2013. The aim ofthis study was to determine how the compensation, working conditions, and the performance of employees inPatra Jasa Jakarta, as well as to determine the effect of compensation and work environment either partially orsimultaneously on the performance of employees in Patra Jasa Jakarta. This type of research is